2019
DOI: 10.1002/bin.1691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating video modeling and video modeling with video feedback to enhance the performance of competitive dancers

Abstract: This study evaluated the use of video modeling and video modeling plus video feedback to enhance four adolescents' performance of a dance movement. Intervention was evaluated in a multiple baseline across participants design. This study found that video modeling enhanced performance from baseline, but the addition of video feedback produced further increases. For one participant, improvement was dependent on the perspective of the video model. Implications of these findings and suggestions for future research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 26 publications
5
26
0
Order By: Relevance
“…The outcomes of the behavioral coaching procedures used in this study in improving student dance performance are similar to results reported in previous research on auditory feedback (Quinn et al, 2015b), public posting (Quinn et al, 2017b), video modeling with video feedback (Quinn et al, 2020), and peer auditory feedback (Quinn et al, 2017a). The results suggest that the manualized POINTE Program may have the potential to be a feasible and useful tool for dance instructors to train students with minimal reliance on a researcher or behavior analyst.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The outcomes of the behavioral coaching procedures used in this study in improving student dance performance are similar to results reported in previous research on auditory feedback (Quinn et al, 2015b), public posting (Quinn et al, 2017b), video modeling with video feedback (Quinn et al, 2020), and peer auditory feedback (Quinn et al, 2017a). The results suggest that the manualized POINTE Program may have the potential to be a feasible and useful tool for dance instructors to train students with minimal reliance on a researcher or behavior analyst.…”
Section: Discussionsupporting
confidence: 82%
“…The researchers found that the coaching procedures increased dance skills across all four dancers. Additional studies on behavioral coaching in dance evaluated TAGteach (Quinn et al, 2015b), peerimplemented TAGteach (Quinn et al, 2017a), public posting with graphical feedback (Quinn et al, 2017b), and video modeling with video feedback (Quinn et al, 2020). Although the aforementioned studies demonstrated positive outcomes for dancers, minimal research currently exists to guide dance instructors in the use of these behavioral coaching procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, variations of video feedback interventions have been extended to evaluate the effectiveness of the interventions to improve dance skills. Quinn et al (2020) evaluated video modeling (VM) alone and a video modeling with video feedback (VMVF) to improve the dance skills of four competitive dancers in a multiple baseline across participants design. The researchers found that VM alone resulted in a small effect on the performance of the skills for the four dancers, but VMVF produced larger increases in performance.…”
mentioning
confidence: 99%
“…If they found VM alone to be insufficient, the coach or trainer may then deem the attention, time, and effort for an added VF component to be worthwhile. Quinn et al (2020) illustrate a good example of this type of assessment. The authors used a multiple baseline design across participants to first evaluate VM, then VM + VF to improve athletic performance for four preteen (aged 9-13 years) competitive dancers.…”
mentioning
confidence: 99%